Report on the BOBCATSSS 2025 Conference – Artificial Intelligence in Library and Information Science - Dani, Erzsébet; Szabó, Dóra (Folia Toruniensia, 2025)
The BOBCATSSS 2025 international conference, held in Istanbul, Turkey (January 21–23, 2025), examined the intersection of artificial intelligence (AI) and library and information science (LIS). Organized by LIS students from Istanbul University, Ankara University, and Gustave Eiffel University, the event drew 200–300 participants from Europe, Asia, and beyond. Keynotes, panels, workshops and case studies discussed AI applications in libraries, ethical and legal challenges, information literacy, knowledge management and open science. Special emphasis was placed on inclusive services, digital exclusion, and algorithmic transparency. Hungarian contributions highlighted national innovations in AI-driven library services. With peer-reviewed presentations and diverse research methods, BOBCATSSS 2025 enhanced academic discussion while promoting networking among students, professionals, and researchers. The conference emphasized the profession’s need to address the ethical, technological and social implications of AI integration.